STUDI PENGARUH WAKTU TINGGAL DAN PENGOLAHAN GANDA TERHADAP PARAMETER AMONIAK, NITRIT DAN NITRAT LINDI DENGAN BIOFILTER SISTEM ANAEROB-AEROB - Alloysius Riza Primadani (Departemen Teknik Lingkungan Fakultas Teknik Universitas Diponegoro, 2013)
Leachate is still an issue that can’t be treated well enough. With a high content of pollutant and lack of government fund support makes landfill administrator must think about the most appropriate treatment that can be good enough before discarding leachate into the environment. Biofilter method is the one of alternatives leachate treatment that can be used. This method does not require a large operating costs and does not require skilled professionals to operate it. The parameters of pollutants that tested in this study are ammonia, nitrite and nitrate. This study is varying the time detention and double-treatment process. From the results can be concluded that the time detention greatly affect the removal efficiency and the double-treatment processs can make greater efficiency.